(untitled) (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Dyslipidemia is one of the major risk factors for ischemic heart disease. Many factors contribute to the development of dyslipidemia. Smoking is one of them. Smoking and dyslipidemia are claimed to interact with each other and synergistically increase the risk of heart disease. The present study is, therefore, intended to find the association between smoking and dyslipidemia in the context of the Bangladeshi population. Methods:The present cross-sectional study was conducted in the Department of Biochemistry, Rajshahi Medical College (RMC), Rajshahi in collaboration with the Institute of Biological Science, Rajshahi University, Rajshahi over a period of five years between 2017 and 2022. A total of 230 adult (ranging from 30 to 60 years) male subjects who attended at Biochemistry Lab of RMC to have their blood tested for lipid profile were consecutively included in the study. However, individuals with the habit of chewing tobacco, ex-smokers, or those having any diseases influencing lipid profile, taking drugs (like β-blockers, thiazide, statins, fibric acid derivatives, and nicotinic acid) that may influence lipid profile, or obese persons under dietary restrictions were excluded from the study. The subjects who exhibited either serum TC: HDL ratio > 4.5 or serum Tg: HDL ratio > 3.5 or both conditions were considered as cases and the subjects who did not have either of the conditions were considered as controls in the present study. Result: In the present study, over one-third (34.8%) of subjects had a smoking habit with the mean duration of smoking being 13.6 ± 5.0 years. Dyslipidaemia (as defined by serum TC: HDL > 4.5) was found in 33% of subjects, while the same condition, defined by serum Tg: HDL > 3.5, was found in 42.6% of the subjects. While either of the two conditions was present in 13% of subjects, both conditions were concurrently observed in 31.3% of subjects. Of the total 230 subjects, 102(44.3%) were dyslipidaemic. Smoking habit was observed to be significantly higher in the case group (54.9%) than that in the control group (18.8%). The risk of having dyslipidaemia in smokers was > 5-fold (95% CI = 2.9 – 9.5) higher than that in non-smokers (p < 0.001). However, as the duration of smoking was correlated with different lipid profiles, it was not found to be significantly correlated with any of the lipid profiles. Conclusion: The study concluded that smokers are more likely to have dyslipidaemia than non-smokers. The risk of having dyslipidaemia in smokers is much higher than that in non-smokers. While serum total cholesterol, low-density lipoprotein (LDL) and serum triglycerides are increased, serum high-density lipoprotein (HDL) is reduced. Ibrahim Card Med J 2023; 13 (1&2): 26-31